2014
DOI: 10.1016/j.jval.2014.08.714
|View full text |Cite
|
Sign up to set email alerts
|

Projection of Long Term Health-Economic Benefits of Sensor Augmented Pump (Sap) Versus Pump Therapy Alone (Csii) In Type 1 Diabetes, A Uk Perspective

Abstract: reduction in diabetes related complications and the lower frequency of SMBG tests. Remaining extra annual costs for SAP were 1,258 € per patient. When indirect costs were considered, the ICER was reduced to 23,300 € per QALY. ConClusions: Using a well-accepted simulation model in an uncontrolled T1DM, projection of the improvement in HbA1c of SAP versus CSII translated into cost-effective ratio, generally considered as very good value for money in France. Extensive sensitivity analysis on key drivers confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In several studies in individuals living with T1D, HCL systems have been found to be a cost‐effective treatment option compared with intermittently scanned CGM plus MDI or CSII or SAP 13‐35 (Table 1). In these studies, CSII was associated with a gain in quality‐adjusted life‐years (QALYs) ranging between 0.35 and 3.1 compared with MDI.…”
Section: Cost‐effectiveness Of Insulin Pump Treatment In T1dmentioning
confidence: 99%
See 1 more Smart Citation
“…In several studies in individuals living with T1D, HCL systems have been found to be a cost‐effective treatment option compared with intermittently scanned CGM plus MDI or CSII or SAP 13‐35 (Table 1). In these studies, CSII was associated with a gain in quality‐adjusted life‐years (QALYs) ranging between 0.35 and 3.1 compared with MDI.…”
Section: Cost‐effectiveness Of Insulin Pump Treatment In T1dmentioning
confidence: 99%
“…Higher mean lifetime costs were estimated, but these costs were partially mitigated thanks to the reduction in short‐ and long‐term diabetes complications, thus treatment costs in the CSII group were linked to the estimated reductions in diabetes‐related complication costs. These studies showed an incremental cost‐effectiveness ratio (ICER) ranging from €11 612 to €44 982 per QALY gained and an ICER below the willingness‐to‐pay threshold was shown for the following countries: Austria, Denmark, Greece, France, Italy, Poland, Spain, Sweden, the Netherlands, Turkey, and the United Kingdom 13‐35 . Greater reductions in HbA1c and fewer severe hypoglycaemic events lead to improved life expectancy and quality‐adjusted life expectancy over the long term.…”
Section: Cost‐effectiveness Of Insulin Pump Treatment In T1dmentioning
confidence: 99%
“…According to systematic reviews, potential benefits of SCI include improved glycaemic control, reduction in the hypoglycaemia unawareness, lower insulin doses, high absorption, and a lower frequency of severe hypoglycaemia [59][60][61]. Due to the development of sensor augmented insulin therapy with or without suspend functions [62,63], the T1DM control and quality of life for patients have significantly enhanced [64,65]. Moreover, SCI is most successful in individuals motivated to manage their condition and supported by a multidisciplinary team with expertise in the delivery of SCI [66].…”
Section: Subcutaneous Versus Inhaled Insulinmentioning
confidence: 99%
“…1 3 improvement in diabetes control, or in quality of life, when comparing to MDI [9], other studies demonstrate improved life expectancy [10] and quality of life with CSII [3]. The field is rapidly progressing and the development of sensoraugmented insulin therapy with or without suspend functions [11,12], and the introduction of a hybrid closed-loop system has the potential to further improve diabetes control and quality of life for people with T1DM [13,14]. Moreover, CSII is most successful in individuals motivated to manage their condition and supported by a multidisciplinary team with expertise in delivery of CSII [15].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%